OPTIMALISASI KEPUASAN KERJA GURU: PERAN STRATEGIS KOMPENSASI DAN LINGKUNGAN KERJA DI SMAS ISLAM ZULKIFLIYAH KECAMATAN SIMPANG MAMPLAM KABUPATEN BIREUEN - Yusuf, M.; Ariska, Emalia; Muchsin, Muchsin; Mulyadi, Mulyadi; Zalikha, Zalikha (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Job satisfaction is a pleasant or positive emotional state resulting from the appraisal of one's job or work experiences. The purpose of this research is to determine the influence of compensation and work environment on the job satisfaction of teachers at SMAS Islam Zulkifliyah, Simpang Mamplam Subdistrict, Bireuen Regency. The research method used is quantitative with a census sampling approach, involving 39 teachers as respondents. Data were collected through questionnaires with a Likert scale of 1-5. The data analysis technique used Multiple Linear Regression and was analyzed using SPSS 24 software. The research results show that compensation and work environment, both partially and simultaneously, have a positive and significant influence on teacher job satisfaction. Compensation, which includes salary, allowances, and incentives, as well as a conducive work environment, has been proven to increase teacher job satisfaction. This research concludes that both factors play an important role in creating teacher job satisfaction, which has a positive impact on the quality of education. This research recommends increasing compensation and creating a supportive work environment to enhance teacher job satisfaction.